2011
DOI: 10.1002/rra.1352
|View full text |Cite
|
Sign up to set email alerts
|

The effects of short‐term inundation on carbon dynamics, microbial community structure and microbial activity in floodplain soil

Abstract: A mesocosm study was carried out to determine whether flooding affected soil microbial structure and function. Over a 24 day period soils were either flooded or remained dry and changes in the microbial community structure, microbial metabolic activity (determined by looking at soil respiration rates and exo-enzyme activity), community level physiological profiles and soil carbon speciation were examined. Flooding induced significant changes in the microbial community structure and increased soil respiration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 59 publications
6
60
1
Order By: Relevance
“…In the soil, contrary to the studies of Wilson et al (2011) and others, we found only minor changes in the community structure caused by flooding. In Wilson et al (2011), the duration of the flood was considerably longer, so we suspect that short-term floods as in our study do not allow for successful establishment of taxa, whereas longer flooding periods may support the colonization and establishment of allochthonous taxa.…”
Section: Flooding As a Factor For Organism Exchange And Shifts In Comcontrasting
confidence: 99%
See 2 more Smart Citations
“…In the soil, contrary to the studies of Wilson et al (2011) and others, we found only minor changes in the community structure caused by flooding. In Wilson et al (2011), the duration of the flood was considerably longer, so we suspect that short-term floods as in our study do not allow for successful establishment of taxa, whereas longer flooding periods may support the colonization and establishment of allochthonous taxa.…”
Section: Flooding As a Factor For Organism Exchange And Shifts In Comcontrasting
confidence: 99%
“…In Wilson et al (2011), the duration of the flood was considerably longer, so we suspect that short-term floods as in our study do not allow for successful establishment of taxa, whereas longer flooding periods may support the colonization and establishment of allochthonous taxa. Interestingly, the similarity between control and flooded treatment of soil even increased after the initial flooding.…”
Section: Flooding As a Factor For Organism Exchange And Shifts In Commentioning
confidence: 70%
See 1 more Smart Citation
“…This suggests that restoration has led to a significant increase in soil functional diversity. These results are in line with previous reports that short-term inundations are important drivers of microbial habitat structure and function in floodplains (Wilson et al, 2011). In a comprehensive study of nitrogen cycling in floodplain soils, we identified two FPZs in the restored section as hot zones of nitrogen turnover and removal : (i) the low-lying alluvial forest with a finetextured soil where anaerobic microsites facilitated coupled nitrification-denitrification; (ii) the gravel bars, characterized by frequent inundation and high sediment deposition rates.…”
Section: How Does Morphological Variability Affect Biogeochemical Trasupporting
confidence: 93%
“…Ecosystem services such as provision of plant and animal resources, removal and/or degradation of pollutants, nutrient retention, and carbon (C) storage are tightly linked to organic C dynamics in riparian soils (Hill and Cardaci, 2004;Wilson et al, 2011). Although the need for a fundamental understanding of the factors that drive the processes involved in C cycling in heterogeneous and dynamic systems such as floodplains is recognized, knowledge is still fragmentary (Pacific et al, 2008;Zehetner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%